Physicochemical and Antioxidant Properties of Iranian Commercial Honeys - Zarei, Mehdi; Fazlara, Ali; Hamedani, Maedeh S. (Current Nutrition & Food Science, 2019)
Background: All over the world, the quality of commercial honeys varies greatly depending on many factors. Hence, this study was conducted to evaluate the physicochemical and antioxidant properties of Iranian commercial honeys to confirm their nutritional and economical quality. Methods: Fifty three honey samples from six different types, including alfalfa, milkvetch, lotus, thyme, coriander and multifloral honeys, were analyzed for pH, free acidity, electrical conductivity, Ash, moisture, hydroxymethylfurfural, reducing sugars, glucose, fructose, proline, color, total phenolic content, ferric reducing antioxidant power and DPPH radical-scavenging activity. Results: In total, physicochemical properties of different honey types were in the range of 4.3 ± 0.49 to 5.2 ± 0.49 for pH, 13.81 ± 2.5 to 26.22 ± 2.8 for free acidity (meq/kg), 15.95 ± 0.45 to 17.98 ± 0.97 for moisture (%), 282.2 ± 50.3 to 578 ± 47 for electrical conductivity (μS/cm), 0.14 ± 0.04 to 0.38 ± 0.03 for ash (g/100 g), 68.66 ± 4.3 to 72.09 ± 6.4 for reducing sugars (g/100 g), 34.67 ± 2.6 to 36.7 ± 2.2 for glucose (g/100 g), 31.9 ± 4.75 to 37.04 ± 4.0 for fructose (g/100 g), 6.1 ± 5.8 to 22.85 ± 10.9 for hydroxymethylfurfural (mg/kg), 426.7 ± 53.91 to 593.9 ± 108.6 for proline (mg/kg), 46.27 ± 4.3 to 96.04 ± 14.4 for color (mm) and 245.4 ± 48.45 to 573.9 ± 69.3 for total phenolic (mg/kg) content. In terms of antioxidant capacity, lotus and thyme honeys were preferable, while the highest level of DPPH radical scavenging activity and ferric reducing antioxidant power were observed in lotus and thyme honeys. Conclusion: These results confirmed that the Iranian commercial honeys meet the quality standards established by national and international regulatory agencies.
Keywords: phenolics